Waves reflected by solid wall in the mixture of liquid with vapour bubbles - Hai, Duong Ngoc; Tuan, Nguyen Van (Vietnam Journal of Mechanics, 2002)
The liquid and gas mixtures are met in many natural and industrial processes. In the paper the results of investigation of waves reflected by solid wall of the stationary shock waves with moderate intensities or the transient pulses propagated in the mixture of liquid with vapour bubbles are presented. The effect of initial conditions, shock strength, size of the bubbles and volume fraction of vapour phase on the behaviour of the waves reflected by solid wall is studied.